Hybrid Sol-gel Coatings to Prevent Corrosion on Hot-dip Galvanized Steel in contact with cementious media - Figueira, R. B. (2013)
Corrosion of reinforcement is one of the prevailing causes of premature deterioration of reinforced concrete. Among the possible anti-corrosion measures, hot-dip galvanized steel extends protection increasing the service life of the rebars in aggressive environments. The zinc layer acts, as a physical barrier that hinders the contact of the aggressive agents with the steel substrate and zinc becomes a sacrificial anode protecting the steel against corrosion even when damage occurs in the concrete. Once the galvanized rebars are placed in contact with fresh concrete (alkaline environment) zinc is attacked by the calcium hydroxide, leading to the formation of calcium hydroxizincate and hydrogen. To reduce the formation of excessive amounts of zinc oxides as well H2 evolution, chromium compounds are usually used in the final concrete mix (≤100 ppm of Cr) or the rebars must be previously passivated with a chromate conversion layer. The high corrosion resistance offered by the use of chromate films is endorsed to the presence of Cr6+, however have been reported to be toxic and carcinogenic, so their application is heavily regulated by environmental legislation and an intense research is being undertaken to replace chromates by eco-friendly compounds. Sol-gel technology revealed to be a successful method in coatings technology and in fabrication of organic-inorganic hybrid (OIH) materials. In this work, four OIH sol-gel matrixes based on functionalized metal alkoxide and oligopolymers, identified as having potential to be an alternative to prevent the corrosion of galvanized steel in concrete were deposited by dip coating method. Surface analysis of coated and uncoated substrate was performed by stereoscopy and SEM/EDS before and after being in contact with cementious media (cement paste and mortar). Monitorization of the galvanic current (jgal) of the coated and uncoated substrates were performed during 74 days only in contact with a mortar.